The number of HLA confirmatory tests during unrelated donor search as a driver for the evaluation of back-up haploidentical donor(s). (August 2020) - Crocchiolo, Roberto; Cornacchini, Giorgia; Lando, Giuliana; Coviello, Arianna; Cuppari, Irene; Volpato, Elisabetta; Pugliano, Maria Teresa; Grillo, Giovanni; Zucchetti, Elisa; Rossini, Silvano
Abstract: Introduction: the identification of a suitable donor in an appropriate timing represents a crucial step in the preparation of allogeneic stem cell transplantation (HSCT). At our Institution, for patients lacking an HLA-identical sibling, a haploidentical donor is considered in the absence of a 10/10-matched or a one-locus HLA-mismatched unrelated donor (UD), but the optimal timing of work-up of potential familiar haploidentical donor(s) by the Apheresis Team is actually unknown. Patients & Methods: we analyzed here n = 167 UD searches launched at our Hospital between July 2013 and July 2018 and looked for any correlation between the number of HLA confirmatory tests received and the final type of donor selected for HSCT, in an attempt to identify those situations where prompt evaluation of haploidentical donor(s) is warranted. Results: a total of n = 117 transplants were performed and haploidentical HSCTs were n = 16 (14 %). In n = 93 cases (56 %) the number of HLA confirmatory tests received were two; they were one, zero and three for n = 52, n = 14 and n = 8 patients, respectively. Only 5 % of haploidentical donors were used when two confirmation test samples were received whereas this percentage rises to 17 % when only one sample reached the HLA lab. When no confirmation tests were available, haploidentical transplant occurred in 100 % of cases. Conclusions: besides the situations with no HLA confirmation tests, the evaluation of any haploidentical donor(s) should be promptly started also when only one HLA confirmatory test is received, in order to optimise the potential work-up process and avoid delay in transplantation.